2011
DOI: 10.1016/j.brainres.2010.10.085
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage is present in the fatal brain edema of diabetic ketoacidosis

Abstract: Oxidative stress is implicated as a pathogenic factor in a spectrum of chronic diseases, notably, neurodegenerative disease. Noteworthy in this regard is that type 1 diabetes mellitus (T1DM) results in oxidative stress, leading to systemic complications of T1DM. We hypothesized that oxidative stress associated with diabetic ketoacidosis (DKA) of T1DM might have measurable brain sequelae. Consistent with this hypothesis are neurohistology and neuroradiologic studies of T1DM that suggest that oxidative insults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 73 publications
2
40
0
Order By: Relevance
“…Oxidative stress markers were elevated in the postmortem brains of two pediatric patients after fatal brain edema associated with DKA (23). Cerebrovascular dysfunction is caused by ROS directly and via tight junction modification and matrix metalloproteinase activation (39).…”
Section: Discussionmentioning
confidence: 98%
“…Oxidative stress markers were elevated in the postmortem brains of two pediatric patients after fatal brain edema associated with DKA (23). Cerebrovascular dysfunction is caused by ROS directly and via tight junction modification and matrix metalloproteinase activation (39).…”
Section: Discussionmentioning
confidence: 98%
“…These disturbances in brain water balance can be viewed as being analogous to those associated with extrapontine myelinolysis, which is typically found in conjunction with fluid/electrolyte disturbances and has been associated with diabetes (21,22). The large U.K. case-control series of DKA-associated cerebral edema did not show an association with any changes in blood glucose after therapy (6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the ketones, especially AA, can generate superoxide radicals and induce cytokine and adhesion molecule expression, and that ketonemic diabetics have high levels of oxidative stress compared to those of normoketonemic diabetic patients [13,14,16,20,24,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54]. We observed that AA was significantly able to upregulate NOX4 expression and NADPH oxidase activity, while BHB failed to produce any adverse effects in HUVEC.…”
Section: Discussionmentioning
confidence: 99%